ANALISA TINGKAT BAHAYA DAN KERENTANAN BENCANA GEMPA BUMI DI WILAYAH NUSA TENGGARA TIMUR (NTT) - Rysnawati, Ni Made; Sukarasa, I Ketut; Alit Paramarta, Ida Bagus (BULETIN FISIKA, 2017)
East Nusa Tenggara is a region in Indonesia which included in the category of hazard prone to earthquakes, because it is flanked by two earthquakes zones, (subduction zone at the south and back arc trust in the north). It is also vulnerable to earthquake disasters because of high population density. These conditions would threaten the safety of lives and property of the population, so it needs to be research to analyze the level of earthquake hazard and vulnerability in East Nusa Tenggara. For identification of the level of hazard and the vulnerability of the earthquake in this study using two factors: the danger factor with indicator Peak Ground Acceleration, vulnerability factors with indicators of population density districts in East Nusa Tenggara. The calculation of the value of PGA use attenuation function of Fukushima and Tanaka. From the calculation of the data obtained that has a very high earthquake hazard is in Ende and Alor district, while the district has a very high risk of vulnerability is in Sikka, Sumba Barat Daya and Sabu Raijua.